Estilos de Vida de los Estudiantes de Odontología de la Universidad Antonio Nariño sede Bogotá - Barreto, Jhon Sebastián; Beltrán, Jorge Andrés; Ortiz Velandia, María Janneth (Universidad Antonio Nariño, 2022)
The objective of this work was to identify the lifestyles of the students of Dentistry of the Antonio Nariño University, in the period 2021 II, the CEVJU-R2 instrument was used, to participate the students gave their informed consent, it was carried out with a group of 82 students, aged between 18 and 30 years, 64 women and 18 men. The following dimensions of diet, physical activity, sleep, alcohol consumption, leisure time, smoking and illegal drugs were taken for analysis. It was found that the lifestyles in this group of students are healthy in dimensions, food with 93%, in alcohol consumption 99%, in physical activity with 54%, and sleep 88%. Student’s exhibit healthy practices in three dimensions such as feeding, drug use, and sleep, in terms of physical activity a higher percentage is evident in men